2021
DOI: 10.1038/s41598-021-92691-1
|View full text |Cite
|
Sign up to set email alerts
|

The global impact of wild pigs (Sus scrofa) on terrestrial biodiversity

Abstract: The International Union for the Conservation of Nature’s (IUCN) Red List of Threatened Species is a comprehensive database of over 120,000 species and is a powerful tool to evaluate the threat of invasive species to global biodiversity. Several problematic species have gained global recognition due to comprehensive threat assessments quantifying the threat these species pose to biodiversity using large datasets like the IUCN Red List of Threatened Species. However, the global threat of wild pigs (Sus scrofa) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 57 publications
0
50
0
1
Order By: Relevance
“…Such damages are not only costly from an economic perspective (Diagne et al, 2020), but they may reduce our productive capacity for food consumption. Beyond agriculture, wild pigs have been shown to have dramatic impacts on terrestrial and freshwater ecosystems as they are thought to have played a role in nearly 30% of assessed species being threatened (Gurevitch & Padilla, 2004) and directly threaten 672 species across 54 countries, many of which are already imperiled (Risch et al, 2021). More specifically, wild pigs have been shown to reduce populations of plants through their rooting behavior, consume eggs of and prey on endangered species, facilitate invasive plant spread, and exacerbate emerging infectious diseases (Barrios‐Garcia & Ballari, 2012; Risch et al, 2021; Zhou et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such damages are not only costly from an economic perspective (Diagne et al, 2020), but they may reduce our productive capacity for food consumption. Beyond agriculture, wild pigs have been shown to have dramatic impacts on terrestrial and freshwater ecosystems as they are thought to have played a role in nearly 30% of assessed species being threatened (Gurevitch & Padilla, 2004) and directly threaten 672 species across 54 countries, many of which are already imperiled (Risch et al, 2021). More specifically, wild pigs have been shown to reduce populations of plants through their rooting behavior, consume eggs of and prey on endangered species, facilitate invasive plant spread, and exacerbate emerging infectious diseases (Barrios‐Garcia & Ballari, 2012; Risch et al, 2021; Zhou et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although wild pigs contribute to global CO 2 emissions, their soil disturbance also affects food security, economic development, and biodiversity protection (Barrios‐Garcia & Ballari, 2012; Risch et al, 2021). While we exclude tillage lands from our analysis to avoid overestimating CO 2 emissions from soil disturbance, wild pigs have been shown to damage important food crops and have indeed been shown to reduce agricultural yields (Barrios‐Garcia & Ballari, 2012) amounting to at least $1.5 billion USD annually in losses and control costs alone (Pimental, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Wild boars are invasive in many parts of the world, including in Latin America, and cause extensive crop damage worldwide ( Bevins et al, 2014 ). They can have deleterious effects on native biodiversity around the globe, even driving some species to extinction ( Risch, Ringma & Price, 2021 ). In our review, all studies focusing on wild boars were from Brazil, where boars have been found to dominate local communities shortly after the invasion ( Doutel-Ribas et al, 2019 ) and consume large amounts of cultivated grain ( Cervo & Guadagnin, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are two species of wild pigs on the island of Java, the wild boar Sus scrofa and Javan warty pig Sus verrucosus (Iskandar 2015;Rustiadi and Prihatini 2015;Frantz et al 2016;Rode-Margono et al 2017;Drygala et al 2020). Globally, wild boars are not classified as an endangered species, and their population increased in the last decade (Risch et al 2021). As endemic to Java, however, Javan warty pig is now classified as an endangered species and has seen dramatic population declines in recent years (Semiadi and Meijaard 2006).…”
Section: Introductionmentioning
confidence: 99%